Upaya Meningkatkan Hasil Belajar Renang Gaya Dada Melalui Media Pembelajaran Pictograph (Department of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this study was to determine how to efforts to improve learning outcomes chest stroke through the medium of learning pictograph in the deaf children class I B in the state SDLB Semarang academic year 2015. This research uses research methods class action research (PTK). In the implementation consists of two cycles. This research subject is deaf student grade I state SDLB Semarang of 10 people consisting of 4 boys and 6 students daughters. instruments used in this study was test performance of students, student observation sheet, and a written test. Based on the results of the study showed the percentage of mastery learning cycle I, phychomotor 10%, affective 40%, cognitive 40%, and mastery learning students in the classical 30% of the total number of students. In the second cycle phychomotor 80%, affective 90%, cognitive 100%, and mastery learning students in the classical 90% of the total number of students. In this research the results of the study showed improve learning outcomes in the classical 60%, cycle I 30 % to 90 % of the cycle II. Based on the results of research on top, it was concluded that the medium of learning pictograph can improved learning outcomes in the deaf children grade I State SDLB Semarang.